PENGARUH AUDIT FEE, KESADARAN ETIS DAN LOCUS OF CONTROL TERHADAP PERILAKU AUDITOR EKSTERNAL - -, Amilin; Desfiandi, Andi (Jurnal Manajemen dan Keuangan, 2009)
This research aimed to identify and to test that influence audit fee, ethics realization and locus of control to external auditorâs behavior. The research has been done in Jakarta with auditor respondent working for public accountant company. Retrieval of sample has been using convenience sampling. Number of questionnaires propagated was 153 copies but only 107 copies question returned and 102 may be used. The data were analysis for hypothesis tester was done with multiple regression.The result of research indicates that audit fee, ethics realization and locus of control have significantly influence to external auditorâs behavior.Keywords: Audit Fee, Ethic Realization, Locus of Control, External Auditorâs Behavior